TAM Approach: Effect of Security on Customer Behavioral Intentions to Use Mobile Banking - Raju Wandira; Ahmad Fauzi (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
As the use of mobile banking continues to grow, attention must be paid to the security of financial transactions. The purpose of this study is to investigate the impact of security levels on the intent of users of mobile banking. This study uses the widely used Technology Acceptance Model (TAM) to investigate user acceptance of information technology. By distributing an online survey, we used mobile banking to collect data from 100 respondents. The data analysis was processed using a SmartPLS application with structural equation modeling (SEM) methods. The results of this analysis show that the security of mobile banking has a significant positive impact on the perceived usefulness of mobile banking. However, security is not the main reason users use mobile banking. This means that customers will continue to use mobile banking, regardless of security. In addition, security does not significantly affect the ease of use of mobile banking. The study also found that the benefits of mobile banking have a significant impact on user intent. The ease of use of mobile banking also has a significant impact on the perceived benefits